Macrobenthos community response to the seasonal hypoxia associated with coastal upwelling off Kochi, along the Southwest coast of India. (15th July 2021) - Pandiya rajan, R.S.; Jyothibabu, R.; Arunpandi, N.; Jagadeesan, L.; Santhi Krishnan, S.; Parthasarathi, S.
Abstract: This study presents the seasonal macrobenthic assemblages in the nearshore environment off Kochi along the southwest coast of India, which is exposed to the freshwater influx, and coastal upwelling associated seasonal hypoxia during the Southwest Monsoon [(SWM) (June–September)]. Monthly observations were made from three locations in different depth zones [inshore (6 m), nearshore (13 m) and coastal (28 m)] along a cross-shore transect off Kochi for one year (2014–15). During the SWM, the study area underwent a significant lowering of salinity in the surface waters due to enhanced freshwater influx and a remarkable oxygen deficiency in the subsurface waters due to upwelling. The Pre-Monsoon [(PRM) (March–May)] macrobenthic community was dominated by gastropods, which transformed into a less diverse and hypoxia adapted opportunistic species of polychaetes ( Paraprionospio pinnata and Cossura coasta ) and foraminifers ( Bolivina sp.) during the SWM. This study showed a seasonal decline of the sensitive fauna and the dominance of opportunistic species as the effect of hypoxia in the study area during the SWM. Highlights: Studied the temporal variations of macrobenthos in the coastal waters off Kochi. Upwelling associated hypoxia was evident in the subsurface waters during the Southwest Monsoon. Gastropods were dominant during the Pre-Monsoon. Hypoxia tolerant and opportunistic macrobenthos dominated during the hypoxia.